The common currency channel of risk sharing - Lindequist, David (Journal of Banking & Finance, 2026)
Conventional wisdom holds that a common currency deprives countries of an important tool for responding to domestic shocks. This paper explores the extent to which a common currency can also facilitate cross-country risk sharing. I develop a monetary model in which asymmetric productivity shocks are partly smoothed through terms-of-trade adjustment and current account imbalances. When these adjustments are incomplete, the central bank can further promote risk sharing by refinancing current account imbalances through an uneven allocation of liquidity across countries. For moderate shocks, this redistribution does not interfere with the inflation target, while large asymmetric shocks create a trade-off between risk sharing and inflation. Applying the model to the 2008–2012 Eurocrisis, I document substantial central-bank-mediated financing of current account imbalances. I find that the common currency channel absorbed roughly one quarter of country-specific output shocks at a time when private markets and fiscal risk-sharing mechanisms were impaired.